Menopausal Symptoms Affecting Productivity and Occupational Needs of Peri-Menopausal Women in a Private University, Philippines - Olivia, J. Factoriza (Journal of Women's Reproductive Health, 2025)
Objective This study aimed to explore the respondents’ reproductive health profiles, examining the physiological and psychosocial perimenopausal symptoms affecting productivity, and identifying occupational needs. It also determined the relationship between menopausal symptoms and the productivity and occupational needs of peri-menopausal women. Methodology A descriptive cross-sectional design was used, surveying 50 women over 40 years old with a validated four-point Likert scale instrument. The instrument undergone content validation, reliability test, and ethical approval. Survey was administered personally and online using purposive sampling. Statistical treatments included weighted mean, F-test, T-test, Pearson r correlation, and ranking. Key results The majority of participants had their first menstruation between 11 to 15 years old and experienced regular menstrual cycles. Most had one child, with an equal number of cesarean and normal deliveries, and reported no pregnancy complications. The study found that participants seldom experienced physiological and psychosocial menopausal symptoms. They agreed on the occupational needs during the perimenopausal period. It was found that physiological symptoms were influenced by factors such as early menarche, cesarean delivery, and pregnancy complications. Additionally, psychosocial symptoms varied based on menstrual status, the number of children, and pregnancy complications, with those experiencing earlier menstruation or complications reporting more intense symptoms. The study revealed a significant relationship between both physiological and psychosocial perimenopausal symptoms, which negatively impacted productivity and increased occupational needs. Women with higher menopausal symptoms expressed a greater need for workplace policies that support perimenopausal women, highlighting the need for tailored workplace interventions for this demographic. Future Direction The study recommends including pap smears and mammograms in annual exams for peri-menopausal women, offering awareness seminars on managing perimenopausal symptoms to reduce workplace disruptions, and suggests future research exploring additional variables affecting perimenopausal women’s health and productivity
Keywords: peri-menopusal women; occupational needs; workplace productivity